War and Institutions: New Evidence from Sierra Leone - Bellows, John; Miguel, Edward (American Economic Review, 2006)
Scholars of economic development have argued that war can have adverse impacts on later economic performance: war destroys physical capital and infrastructure and disrupts human capital accumulation, and it may also damage institutions by creating political instability, destroying the social fabric and endangering civil liberties (World Bank 2003). Understanding war’s impact on development is particularly important for Sub-Saharan Africa, where two-thirds of all nations suffered from armed conflict during the 1980s or 1990s. The proliferation of armed conflict in the world’s poorest region begs the question of what role conflict may be playing in Africa’s disappointing economic performance. Yet the net long run effects of war are ambiguous from the point of view of economic theory. To the extent that war impacts are limited to the destruction of capital, the neoclassical model predicts rapid economic growth postwar converging back to steady state growth. Several recent papers that study war impacts – including in Japan (Donald R. Davis and David E. Weinstein, 2002) and Vietnam (Edward A. Miguel and Gerard Roland 2005) – find few persistent local impacts of U.S. bombing, with heavily bombed areas experiencing rapid recovery to prewar population and economic trends. This is consistent with the neoclassical model if war’s main consequence is to destroy capital. War could also affect long run growth – either positively or negatively – by modifying the scale parameter in the neoclassical growth model. For example, while World Bank (2003) argues that war has adverse institutional consequences, Charles H. Tilly shows how war promoted state formation and nation building in Europe historically, ultimately strengthening institutions (Tilly 1975). 1 In this short paper, we study the aftermath of the recent civil conflict in Sierra Leone. One notable aspect of this project is the extensive household data for Sierra Leone on conflict experiences and on local institutions. Our results are complementary to the other recent studies mentioned above, none of which examines institutional impacts.